Calibration of high performance size exclusion chromatography (HPSEC) for molecular weight estimation of aquatic humic substances. Issue 6 (December 2022) - Mackie, Allison L.; Park, Yuri; Gagnon, Graham A.
Abstract: Three high performance size exclusion chromatography (HPSEC) columns were compared, along with mobile phase chemistry and calibration standards, for the determination of apparent molecular weight (AMW) of aquatic humic substances using a UV absorbance detector (λ = 254 nm). The addition of 10 % organic solvent did not influence peak elution times of sodium polystyrene sulfonate (PSS) standards or chromatograms of Suwannee River humic acid (SRHA) or fulvic acid (SRFA) but did result in an additional peak being detected in a treated municipal wastewater sample (WWT). Mobile phase concentration was found to have a greater effect on peak position of PSS standards and SRHA than mobile phase pH or sample injection volume. Several chemicals of known molecular weight were tested alongside PSS standards, with salicylic acid (138.1 Da) and 4-chlorobenzoic acid (156.6 Da) resulting in retention times that aligned with the PSS MW standards. Of the three columns tested, the two with comparable pore sizes (i.e., 250 and 300 Å) were found to result in similar peak elution times and highly linear calibration curves over the range of 210–17, 000 Da, while the column with the smaller pore size (i.e., 100 Å) gave better peak separation in the low AMW range (i.e., < 1000 Da). Estimations of AMW of SRHA using various sets of calibration standards on one of the three columns tested ranged from 1080 to 2799 Da using 0.02 M NH4 CH3 CO2 as eluent and 60-µL injections. AMW of SRFA ranged from 939 to 2434 Da for the same conditions. Graphical Abstract: ga1 Highlights: 10 % organic solvent in eluent resulted in additional high AMW peak for treated WW. Columns with similar pore sizes performed similarly in terms of peak retention time. Columns with smaller particle size gave better resolution of humic peaks. Salicylic acid and 4-chlorobenzoic acid could be used as calibration standards. SRHA and SRFA AMW estimated to range from 1080 to 7180 and 939–2434 Da.